Meningkatkan Kemampuan Bepikir Kreatif melalui Penerapan Pendekatan Saintifik Berbantuan VBA Excel - Asep Ikin Sugandi; Martin Bernard; Linda Linda (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
The low creative thinking of junior high school students and the lack of use of ICT-based learning media are problems in this study. The research aims to determine the effectiveness of scientific learning with the help of VBA Excel in students' creative thinking. The experimental method is the method used in this study with a Non Equivalent Control Group Design, the samples were taken from two classes in one junior high school in the city of Cimahi. The instrument used is in the form of a creative thinking ability test, which consists of 5 questions. The results in this study conclude that scientific learning with the help of VBA Excel is more effective than ordinary learning in terms of creative thinking skills.